Pengaruh Kinerja Non Keuangan (Environmental, Social, Governance) terhadap Resiko Investasi Perusahaan - Agus Triyani; Suhita Whini Setyahuni; Fiki Durrotul Makwuna (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2021)
This study intends to investigate the impact of sustainability information on the level of firm’s risk. This study uses 103 firms-years observation of public listed companies in Indonesia during 2012 to 2018. Ordinary least squares regression analysis is employed to tested the hypotheses. ESG scores Bloomberg is used as an indicator of sustainability reporting. The theory used in this study is Signaling theory, which is an action taken by the company to provide instructions for investors on how to view the companies prospects. The findings indicate that social information can decrease the level of firm’s risk. Additionally, environmental and governance information have a negative impact on systematic risk only. Neither environmental nor governance information have an impact on non-systematic risk and total risk. This study contributes to the practical implications, especially on how to consider sustainability information on investment’s valuation models. This study also gives a fruitful insight to the literature by giving empirical evidence on the relationship between sustainability information and corporate’s risk.